2021
DOI: 10.1172/jci138315
|View full text |Cite
|
Sign up to set email alerts
|

Mutant SF3B1 promotes AKT- and NF-κB–driven mammary tumorigenesis

Abstract: Mutations in the core RNA splicing factor SF3B1 are prevalent in leukemias and uveal melanoma but hotspot SF3B1 mutations are also seen in epithelial malignancies such as breast cancer. Although hotspot mutations in SF3B1 alter hematopoietic differentiation, whether SF3B1 mutations contribute to epithelial cancer development and progression is unknown. Here, we identify that SF3B1 mutations in mammary epithelial and breast cancer cells induce a recurrent pattern of aberrant splicing leading to activation of AK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 64 publications
1
20
0
Order By: Relevance
“…For some of these genes missplicing was shown to promote tumor malignancy (i.e. MAP3K7, PPP2R5A) (Lieu et al, 2020;Liu et al, 2020;Obeng et al, 2016b), confirming the proto-oncogenic role of SF3B1. Interestingly, recent studies have also found a link between wildtype SF3B1 expression levels and tumor aggressiveness in pancreatic-, endometrial-, prostate-, liver-and breast cancer, with higher expression being associated with adverse prognosis (Alors-Perez et al, 2021;Jiménez-Vacas et al, 2019;López-Cánovas et al, 2021;Popli et al, 2020;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 73%
“…For some of these genes missplicing was shown to promote tumor malignancy (i.e. MAP3K7, PPP2R5A) (Lieu et al, 2020;Liu et al, 2020;Obeng et al, 2016b), confirming the proto-oncogenic role of SF3B1. Interestingly, recent studies have also found a link between wildtype SF3B1 expression levels and tumor aggressiveness in pancreatic-, endometrial-, prostate-, liver-and breast cancer, with higher expression being associated with adverse prognosis (Alors-Perez et al, 2021;Jiménez-Vacas et al, 2019;López-Cánovas et al, 2021;Popli et al, 2020;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 73%
“…Among these mutated codons, K700E is the most common mutation in CLL, MDS, acute myeloid leukemia, and invasive breast carcinoma, while R625 is the predominant mutation in uveal melanoma and skin cutaneous melanoma [31]. Previous studies have explored how the SF3B1 K700E mutation contributes to aberrant splicing and downstream pro-tumorigenesis mechanisms in CLL and breast cancer using cell lines and mouse disease models [31,32]. To understand the molecular and phenotypic consequences of the SF3B1 R625H mutation on prolactinoma tumorigenesis, we generated a heterozygous Sf3b1-R625H mutant rat pituitary cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, mutant SF3B1 induced the inclusion of 16 intronic nucleotides in exon 22 by using an upstream cryptic 3′ splice site in human sequences (Fig. 3A), which may lead to NMD and reduced DLG1 expression, because the shifted reading frame produces a premature termination codon in this alternative spliceform [32]. Despite mutant SF3B1 inducing different splicing events in rats and humans, DLG1 mRNA and protein were downregulated in both models.…”
Section: Discussionmentioning
confidence: 99%
“… [ 239 ] ARID1A/B mutations or deficiency Gastric, ovarian and endometrioid carcinoma, medulloblastoma [ 245 – 247 ] SF3B1 mutation Myelodysplastic/myeloproliferative neoplasms, melanoma, breast cancer, pancreatic cancer, prostate cancer, AML, etc. [ 254 , 255 ] NPM1 mutation AML [ 257 ] NM23-H1 Breast cancer, melanoma, etc. [ 248 ] CBL mutation Myeloid neoplasmas [ 249 ] BTK mutation or deficiency Follicular lymphoma [ 253 ] GPS2 mutation Breast cancer, medulloblastoma [ 250 252 ] CDH1 mutation or deficiency Gastric cancer, breast cancer, prostate cancer, colorectal cancer, ovarian cancer, etc.…”
Section: Biomarkers and Molecular Basis Of Response To Akt Inhibitors In Cancermentioning
confidence: 99%
“…Moreover, mutations in cancer-associated splicing factor 3b subunit 1 (SF3B1) have been detected in hematological malignancies, breast cancer, prostate cancer, pancreatic ductal carcinoma, melanoma and other types of cancer [ 254 ]. SF3B1 mutants cause aberrant mRNA splicing and suppression of PPP2R5A, leading to Akt activation and the hypersensitivity to Akt inhibitors [ 255 ]. Since mutations in another splicesomal gene, SURP and G-patch domain containing 1 ( SUGP1) , induce aberrant splicing identical or similar to that observed in mutant SF3B1 cancers, it remains to know whether SUGP1 mutations also confer hypersensitivity to Akt inhibitors [ 256 ].…”
Section: Biomarkers and Molecular Basis Of Response To Akt Inhibitors In Cancermentioning
confidence: 99%